Chronic Psychosocial Stress in Mice Is Associated With Increased Acid Sphingomyelinase Activity in Liver and Serum and With Hepatic C16:0-Ceramide Accumulation - Reichel, Martin; Rhein, Cosima; Hofmann, Lena M.; Monti, Juliana; Japtok, Lukasz; Langgartner, Dominik; Füchsl, Andrea M.; Kleuser, Burkhard; Gulbins, Erich; Hellerbrand, Claus; Reber, Stefan O.; Kornhuber, Johannes (Frontiers in Psychiatry, 2018)
Chronic psychosocial stress adversely affects human morbidity and is a risk factor for inflammatory disorders, liver diseases, obesity, metabolic syndrome, and major depressive disorder (MDD). In recent studies, we found an association of MDD with an increase of acid sphingomyelinase (ASM) activity. Thus, we asked whether chronic psychosocial stress as a detrimental factor contributing to the emergence of MDD would also affect ASM activity and sphingolipid (SL) metabolism. To induce chronic psychosocial stress in male mice we employed the chronic subordinate colony housing (CSC) paradigm and compared them to non-stressed single housed control (SHC) mice. We determined Asm activity in liver and serum, hepatic SL concentrations as well as hepatic mRNA expression of genes involved in SL metabolism. We found that hepatic Asm activity was increased by 28% (P-value = 0.006) and secretory Asm activity by 47% (P-value = 0.002) in stressed mice. C16:0-Cer was increased by 40% (P-value = 0.008). Gene expression analysis further revealed an increased expression of tumor necrosis factor (TNF)-α (P-value = 0.009) and of several genes involved in SL metabolism (Cers5, P-value = 0.028; Cers6, P-value = 0.045; Gba, P-value = 0.049; Gba2, P-value = 0.030; Ormdl2, P-value = 0.034; Smpdl3B; P-value = 0.013). Our data thus provides first evidence that chronic psychosocial stress, at least in mice, induces alterations in SL metabolism, which in turn might be involved in mediating the adverse health effects of chronic psychosocial stress and peripheral changes occurring in mood disorders.